The alchemy of happiness in Noordin Hassan's "Tonight, The Turtles Cry" - Mohd Ramli, Aimillia; Abdul Halim, Norfarihin (Dewan Bahasa dan Pustaka, 2020)
Current interest in the nature of happiness hasve made it a new focal point in the study of literature not to mention sustainable development. While in the West it has been analysed in relation tolight the dramatic form of tragedy, there has been no corresponding research, as far as we know, on it within the context of Islamic theater. As the founder of teater fitrah , an Islamic brand of theatre, Noordin Hassan and his plays could prove to be fertile grounds from which the issue of happiness could be explored. Hence, this paper aims to discuss Noordin’s Tonight, the Turtles Cry (1994) from an Islamic conceptual framework for happiness as derived from two philosophers, al-Ghazali and al-Attas. al-Ghazali’s The Alchemy of Happiness (1910) and Iĥyā' 'Ulūmiddīn (1982) as well as al-Attas’ The Meaning and Experience of Happiness (2014) provide the main theoretical texts from which this framework is taken. Elements of this framework consists of the following: knowing oneself, knowing Allah (s.w.t.), knowing this world, which includes ways on building and developing one’s relationship with one’s family and community, as well as having an appreciation for nature and, finally, having a strong conviction in the Hereafter. The analysis used is through close reading of the text. The findings of this articlepaper show significant aspects of Noordin’s play as being reflectingve of these components of happiness and, in addition to showcasing values that are needed to sustain the wellbeing of a person.